filament nozzle extruder for polylactic acid (PLA) material - Sukindar, Nor Aiman (2016)
The present invention relates generally to a 3D printer extruder for domestic usage. There is a known 3D printer extruder comprising of liquefier, nozzle and insulator for printing three dimensional product. However, the extruder is not specifically design for polylactic acid (PLA) material, thus producing instability and inaccurate of10 extrusion process. The present invention discloses a 3D printer extruder comprising of a liquefier (5) in cylindrical shape having a nozzle slot (6), tiny screw hole (1), heating element slot (3), an insulator (2)which is made form fibre glass coated material enclosing said liquefier (5) , a nozzle (4) attached to said nozzle slot (6) having a die angle range in between 110° to 130°.